Lucio phenomenon: a case report on an overlooked reaction in lepromatous leprosy - Sajjachareonpong, Natsuda; Sudtikoonaseth, Poonnawis; Kampirapap, Kowit; Tanabodee, Monton; Prunglumpoo, Sutsarun; Kiatsurayanon, Chanisa (Dermatology Reports, 2025)
Our patient presented with a 5-year history of chronic, asymptomatic papulonodular lesions on the extremities. Over the past 8 months, the lesions have spread to the face and earlobes, and new ulcerative lesions have appeared on both legs. Skin biopsy was compatible with lepromatous leprosy with Lucio phenomenon. Lucio phenomenon is a rare type of leprosy reaction found mostly in neglected lepromatous leprosy cases. Unfortunately, the patient developed pulmonary embolism and passed away. This case report focuses on the clinicopathological characteristics and management of Lucio phenomenon, which is an unusual form of leprosy reaction that often carries a poorer prognosis. Importantly, physicians should be able to differentiate the Lucio phenomenon from other types of leprosy reactions for prompt management.